Azole-resistance screening in occupational exposure assessments to mycobiota - Caetano, Liliana Aranha (2018)
Exposure to azole-resistant fungal species in workplaces represents a health risk for workers. This study describes the prevalence of azole-resistant mycobiota in three occupational environments, namely, bakeries, waste industry, and swine farms, and it proposes complementary sampling methods for the evaluation of occupational exposure to azole-resistant mycobiota at critical worksites.